How to calculate median Pregnancy-Associated Plasma Protein-A values to predict preeclampsia? Do We Need a Newer Formula? - Karamustafaoğlu Balcı, Burçin; Kalelioğlu, İbrahim Halil and Kılıç, Yusuf and Has, Recep and Ömer, Beyhan (Gynecology Obstetrics & Reproductive Medicine, 2016)
Objective: Preeclampsia is one of the major issues in maternal–fetal medicine. Early risk stratification may be beneficial, so is the aim of several researches. Our goal is to investigate whether PAPP-A MoM calculated for first trimester Down’s syndrome screening or MoM calculated according to Ong’s formula can be used to predict the risk of preeclampsia or do we need another method to calculate PAPP-A MoM derived from non preeclamptic cases. Study Design: For this retrospective study, data of randomly selected 150 singleton pregnant women who did not develop preeclampsia are used to create a formula to calculate median value of PAPP-A. PAPP-A values of this subgroup are plotted against gestational age and curve fit analysis is done to determine best fitted regression line to get a formula to calculate median value of our cases. PAPP-A MoM values are calculated for each subject according to Ong’s formula and our formula. We already had MoM values derived from first trimester screening. ROC curve and Delong’s pairwise comparison analyses are used to investigate which MoM value is more predictive for preeclampsia. Results: Although the area under curve value of MoM values derived from this study was the highest, DeLong’s pairwise comparison analysis showed no statistically significant difference between the three curves. Conclusion: PAPP-A MoM calculation specific to preeclampsia does not seem to be necessary; PAPP-A MoM obtained from first trimester aneuploidy scan can be used to predict preeclampsia.